The politics of quotation: Charlotte Smith’s radical fictions and their allusions to the works of Milton, Rousseau, and Voltaire - Fernandez, LE (2020)
Charlotte Smith is both a known radical sympathizer and an allusive writer. This thesis investigates the political meanings embedded through the selection and treatment of allusion in each of Charlotte Smith’s novels published between the outbreak of the French Revolution and the end of the Reign of Terror. Specifically, it investigates how Smith utilizes quotations from authors connected with political radicalism—John Milton, Voltaire, and Jean-Jacques Rousseau—to work through the nuances of her own political thought. I argue that these specific authors feature significantly in her work because of their known republican sympathies. Yet, Smith frequently deploys these quotations in a context far from that which was originally intended by her source, capitalizing on their republican significations but making the actual polemical content all her own. Both the frequency and diversity of her allusive engagement increases during the period of the Revolution, which marks the Revolutionary period as one essential to the development of Smith as both a novelist and as a radical. Through tracking the presence of quotation in each novel, one published each year between 1791 and 1794, the thesis traces the evolution in Smith’s political thought and, specifically, her changing attitudes toward the French Revolution as it moves through its early utopian stages to the violence and excess of the Reign of Terror. Not only does this study contribute to recent scholarship on the use of quotation in eighteenth-century writing, but it also provides an in-depth study of Smith’s evolving radicalism. In this way, the project demands reassessment of critical studies of Smith’s work which have failed to recognize the extent of the polemical content within the first work in the sequence, Celestina, and the continuing commitment to republican sympathies despite burgeoning conservatism in the last, The Banished Man.